There Is No Special Problem About Scientific Representation - Craig CALLENDER; Jonathan COHEN (Theoria, 2010)
We propose that scientific representation is a special case of a more general notion of representation, and that the relatively well worked-out and plausible theories of the latter are directly applicable to the scientific special case.